Rancang Bangun Media Pembelajaran Alat Musik Senibudaya Minangkabau Mengguanakan Touch Sensor Berbasis Arduino Mega 2560 Dan Smartphone - Rifqa Suchiayana Putri; Guslendra; Hadi Syahputra (Journal of Computer Scine and Information Technology, 2023)
The learning process of Minangkabau cultural musical instruments is still carried out using book references and direct interaction with musical instruments to understand and comprehend the explanations of the existing musical instruments in Minangkabau culture. The learning process involves introducing each musical instrument one by one. Problem identification, data collection, system analysis, instrument system design, system testing using the designed instrument will provide an explanation of the learning process for introducing Minangkabau cultural musical instruments using Arduino Mega 2560 and a smartphone, which may offer insights into the material and sound of these musical instruments. The touch sensor utilized can facilitate the selection of musical instruments by simply touching, and the Arduino Mega 2560 employed can control the multimedia learning system for introducing musical instruments.